2014
DOI: 10.1590/s0036-46652014000400017
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR IDENTIFICATION OF Bartonella henselae IN A SERONEGATIVE CAT SCRATCH DISEASE PATIENT WITH AIDS IN RIO DE JANEIRO, BRAZIL

Abstract: Bartonella henselae is associated with a wide spectrum of clinical manifestations, including cat scratch disease, endocarditis and meningoencephalitis, in immunocompetent and immunocompromised patients. We report the first molecularly confirmed case of B. henselae infection in an AIDS patient in state of Rio de Janeiro, Brazil. Although DNA sequence of B. henselae has been detected by polymerase chain reaction in a lymph node biopsy, acute and convalescent sera were nonreactive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…With direct detection or antibody research, B. henselae has already been identified in cats in the states of Maranhão (de Oliveira Braga et al 2012 ), Pernambuco (Fontalvo et al 2017 ); Bahia (Costa et al 2014 ), Mato Grosso (Miceli et al 2013 ), Mato Grosso do Sul (André et al 2016 ), Rio de Janeiro (Crissiuma et al 2011 ; Kitada et al 2014 ; da Silva et al 2018 ), São Paulo (Bortoli et al 2012 ; Drummond et al 2018 ), and the Rio Grande do Sul (Staggemeier et al 2014 ; Malheiros et al 2016 ). Similarly, the microorganism has been found in humans in the states of Rio de Janeiro (Lamas et al 2013 ; Favacho et al 2014 ), São Paulo (Vieira-Damiani et al 2015 ; Drummond et al 2018 ), and Minas Gerais (Da Costa et al 2005 ). Interestingly, studies conducted in Brazil have demonstrated the presence of Bartonella spp.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…With direct detection or antibody research, B. henselae has already been identified in cats in the states of Maranhão (de Oliveira Braga et al 2012 ), Pernambuco (Fontalvo et al 2017 ); Bahia (Costa et al 2014 ), Mato Grosso (Miceli et al 2013 ), Mato Grosso do Sul (André et al 2016 ), Rio de Janeiro (Crissiuma et al 2011 ; Kitada et al 2014 ; da Silva et al 2018 ), São Paulo (Bortoli et al 2012 ; Drummond et al 2018 ), and the Rio Grande do Sul (Staggemeier et al 2014 ; Malheiros et al 2016 ). Similarly, the microorganism has been found in humans in the states of Rio de Janeiro (Lamas et al 2013 ; Favacho et al 2014 ), São Paulo (Vieira-Damiani et al 2015 ; Drummond et al 2018 ), and Minas Gerais (Da Costa et al 2005 ). Interestingly, studies conducted in Brazil have demonstrated the presence of Bartonella spp.…”
Section: Introductionmentioning
confidence: 93%
“…Serologies show a prevalence of 15–56.6% in cats (Crissiuma et al 2011 ; Kitada et al 2014 ; Fontalvo et al 2017 ) and 3.2–23.5% in humans (Pitassi et al 2015 ; Vieira-Damiani et al 2015 ). Molecular methods have revealed the prevalence to be 2.2–90.2% in cats (Staggemeier et al 2014 ; Malheiros et al 2016 ; Drummond et al 2018 ) and 3.2–100% in humans (Lamas et al 2013 ; Favacho et al 2014 ; Pitassi et al 2015 ; Vieira-Damiani et al 2015 ). With direct detection or antibody research, B. henselae has already been identified in cats in the states of Maranhão (de Oliveira Braga et al 2012 ), Pernambuco (Fontalvo et al 2017 ); Bahia (Costa et al 2014 ), Mato Grosso (Miceli et al 2013 ), Mato Grosso do Sul (André et al 2016 ), Rio de Janeiro (Crissiuma et al 2011 ; Kitada et al 2014 ; da Silva et al 2018 ), São Paulo (Bortoli et al 2012 ; Drummond et al 2018 ), and the Rio Grande do Sul (Staggemeier et al 2014 ; Malheiros et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Na história epidemiológica, o paciente relatava contato com animal doméstico e a suspeita de infecção por Bartonella spp. foi confirmada por análise molecular (FAVACHO et al, 2014).…”
Section: Bartonelas E a Bartonelose No Brasilunclassified